2008
DOI: 10.1038/nature07061
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells induced from adult neural stem cells by reprogramming with two factors

Abstract: Reprogramming of somatic cells is a valuable tool to understand the mechanisms of regaining pluripotency and further opens up the possibility of generating patient-specific pluripotent stem cells. Reprogramming of mouse and human somatic cells into pluripotent stem cells, designated as induced pluripotent stem (iPS) cells, has been possible with the expression of the transcription factor quartet Oct4 (also known as Pou5f1), Sox2, c-Myc and Klf4 (refs 1-11). Considering that ectopic expression of c-Myc causes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
672
1
20

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 876 publications
(710 citation statements)
references
References 26 publications
17
672
1
20
Order By: Relevance
“…Among the four factors, c-Myc is not necessary for the reprogramming of somatic cells into iPSCs [45,46]. Furthermore, recent studies have shown that both mouse and human neural stem cells can be reprogrammed to iPSCs with Oct4 and Klf4, or Oct4 alone [47][48][49]. However, neural stem cells express endogenous Sox2, suggesting that Sox2 and Oct4 are sufficient for iPSC induction, while Klf4 and c-Myc may act to enhance the efficiency of this induction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four factors, c-Myc is not necessary for the reprogramming of somatic cells into iPSCs [45,46]. Furthermore, recent studies have shown that both mouse and human neural stem cells can be reprogrammed to iPSCs with Oct4 and Klf4, or Oct4 alone [47][48][49]. However, neural stem cells express endogenous Sox2, suggesting that Sox2 and Oct4 are sufficient for iPSC induction, while Klf4 and c-Myc may act to enhance the efficiency of this induction.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Myc to bind to a staggeringly large number of genomic loci has also been demonstrated in ES cells [16] and is likely to underlie its activity as part of the "magic quartet" of transcription factors that can reprogram somatic cells to pluripotency [1; 17; 18; 19]. High levels of Myc may block cell differentiation and enhance self-renewal of committed and differentiated cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neural stem cells were successfully re-programmed by using only oct4 and klf4 transcription factors upon determining that these cells already present sox2 and c-myc. 31 It seems that endogenous expression levels of transcription factor genes such as oct4, klf4, sox2 and c-myc in adult cells are very important for re-programming adult cells to induced pluri-potent stem cells. 29 The expression levels of these genes have not yet been characterized in human tooth germ stem cells (hTGSCs).…”
Section: Introductionmentioning
confidence: 99%